Hepatotoxicity risk factors in HIV-infected MSM with HBV/HCV coinfections: A cohort study in Northwestern China - Xinyu Ma; Ruimin Bai; Zirong Zhu; Tongquan Wang; Xinrong Zhao; Yan Sun; Yan Zheng (PLoS ONE, 2025)
Objective To evaluate the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) coinfections among human immunodeficiency virus (HIV)-infected men who have sex with men (MSM) initiating their first antiretroviral therapy (ART) in Northwestern China, and to examine the impact of coinfections on hepatotoxicity risk. Methods This retrospective cohort study analyzed MSM who were newly diagnosed with HIV and initiated ART in Northwestern China between January 1st, 2005, and June 30th, 2019. A total of 4,690 MSM aged ≥18 years were included and categorized into three groups based on HBV or HCV coinfection status: HIV monoinfection, HIV/HBV coinfection, and HIV/HCV coinfection. Hepatotoxicity was classified into grades 0 (normal) to 4 (life-threatening) according to the degree of elevation in liver enzymes (AST or ALT). Kaplan-Meier curves were used to evaluate the incidence of hepatotoxicity, mortality, and ART failure rates, while Cox proportional hazards models assessed the independent impact of coinfections on hepatotoxicity risk. Results Among 4,690 HIV-infected MSM, the prevalence of HIV/HBV and HIV/HCV coinfections was 5.18% and 2.17%, respectively. Coinfected individuals had significantly elevated hepatotoxicity risks. HIV/HBV coinfection substantially increased the risk of any-grade hepatotoxicity (Hazard Ratio [HR]: 1.190, 95% Confidence Interval [CI]: 1.029–1.375) and grade ≥3 hepatotoxicity (HR: 3.161, 95% CI: 2.095–4.769). HIV/HCV coinfection was also associated with a higher risk of any-grade hepatotoxicity (HR: 1.311, 95% CI: 1.050–1.636). Older age at ART initiation, a shorter diagnosis-to-treatment interval, and HBV/HCV coinfection were identified as risk factors, while higher CD4 + T lymphocyte counts and lower hemoglobin levels were protective factors. Conclusion HIV/HBV and HIV/HCV coinfections significantly increased the risk of hepatotoxicity in HIV-infected MSM receiving ART. These findings underscore the importance of vigilant liver function monitoring in coinfected patients on ART, particularly in consideration of baseline factors such as age, time to treatment, CD4 + T-cell count, and hemoglobin level, to minimize interruptions and optimize outcomes.